Adaptive RS-group scheduling for WiMAX multihop relay - Saeed, Rashid Abdelhaleem; Al-Talib , S.A.; Al-Ahdal, T.A.; Mohamad, H.; Abbas, Majed; Ali, Bashir; Odeh, M. (2010)
IEEE 802.16j Multihop Relay (MR) is an optional deployment introduced to enhance the coverage and performance of WiMAX network without the need for deploying costly Base Stations (BSs). Multihop Relay network comprises of Multihop Relay BS (MRBS) and Relay Stations (RSs). This paper proposes mesh topology for IEEE 802.16j using adaptive RS group scheduling. The proposed scheduling algorithm introduces new signalling to support functions such as soft and hard horizontal-RS neighbour scanning, bandwidth request, forwarding of PDUs and connection management. The proposed model is evaluated using NS-2 network simulation. The simulation result shows that the proposed scheduling achieves higher throughput performance compared to IEEE 802.16j tree-topology.